Efektifitas Pembelajaran Steam Berbasis Hots dalam Meningkatkan Kemampuan Problem Solving Anak Usia 5-6 Tahun - Wuni Arum Sekar Sari; Wiwin Hidayati (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to determine the effectiveness of implementing STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning based on HOTS (Higher Order Thinking Skills) in improving problem-solving abilities in children aged 5–6 years at RA Roudlotul Huda Baleturi Prambon. This research employs classroom action research (CAR) with a cyclical design consisting of two cycles. Each cycle includes four phases: planning, implementation, observation, and reflection. The pre-survey conducted on February 5, 2024, showed that 50% of the children still had difficulty solving everyday problems and tended to rely on others. In Cycle 1, out of 12 students, 7 students (58%) showed expected development, and 5 students (42%) were beginning to develop, with an average class score of 9.25. In Cycle 2, there was a significant improvement, with 10 students (83%) achieving very good development and 2 students (17%) showing expected development. Based on the results, it can be concluded that STEAM learning based on HOTS is effective in improving early childhood problem-solving skills, with active teacher involvement and the use of engaging media as supporting success factors. This study recommends the application of similar learning models in early childhood education to foster children's critical and creative thinking skills